Mengapa Perusahaan Manufaktur Di Indonesia Melakukan Keputusan Hedging? - Arinal Mirdha; Muhammad Arfan; Indayani (Jurnal Reviu Akuntansi dan Keuangan, 2023)
Purpose: This study aims to examine the factors that influence manufacturing companies in Indonesia to make hedging decisions Methodology/approach: The study selected 179 companies as the population and 124 companies as a sample. The analysis unit used is a manufacturing company listed on the Indonesia Stock Exchange for the 2018-2020 observation year, so that the observation unit amounted to 372 observations. The study sample was selected using a simple random sampling technique. The source of this research data is secondary data obtained from the publication of the company's annual financial statements and analyzed using logistic regression. Findings: The results showed that growth opportunities and financial leverage are factors that motivate company managers to make hedging decisions, while likiudity is a factor that mitigates managers to make hedging decisions. On the other hand, cash flow volatility is a factor that is unable to explain hedging decisions. Practical implications: Practical implications in this study suggest that when making hedging decisions, manufacturing company managers should consider factors that influence hedging decisions, namely growth opportunities, financial leverage, and liquidity. Additionally, investors and creditors should also take into account variables or factors that influence manager decisions on hedging before deciding to invest or provide loans. Originality/value: This study used simple random sampling techniques in determining research samples, in contrast to previous studies that used purposive sampling techniques. This aims to overcome the weaknesses of purposive sampling techniques that are not able to generalize results of study to the entire population.